2004
DOI: 10.3184/0308234042430458
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazolic tripods synthesis and cation binding properties

Abstract: The synthesis of two new bipyrazolic tripods with different functionalised arms is described. The complexing properties of these compounds towards heavy metal ions (Hg2+, Cd2+, Pb2+) and alkaline metal ions (K+, Na+, Li+) were studied by a liquid–liquid extraction process and the extracted cation percentage was determined by atomic absorption measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 11 publications
3
14
0
Order By: Relevance
“…In our laboratory, a number of pyrazole based tripodal ligands have been studied . These ligands incorporating in their structures two sp 2 and sp 3 hybridized amine nitrogen atoms, could be distinguish according to their side arms and the nature of junctions (N–C–N or N–C–C) that bound the pyrazole ring to the lateral arm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our laboratory, a number of pyrazole based tripodal ligands have been studied . These ligands incorporating in their structures two sp 2 and sp 3 hybridized amine nitrogen atoms, could be distinguish according to their side arms and the nature of junctions (N–C–N or N–C–C) that bound the pyrazole ring to the lateral arm.…”
Section: Introductionmentioning
confidence: 99%
“…These ligands incorporating in their structures two sp 2 and sp 3 hybridized amine nitrogen atoms, could be distinguish according to their side arms and the nature of junctions (N–C–N or N–C–C) that bound the pyrazole ring to the lateral arm. Therefore, they were found in several fields such as catalysis, extraction of heavy metals and pharmacology . However, some studies have reported that such ligands present no antibacterial activities similarly to the thiophene tripods .…”
Section: Introductionmentioning
confidence: 99%
“…In all the cases, we note that these two membranes present an interesting phenomenon of transport towards the transition metal cations compared with the previous membranes10–12 incorporating the mono‐ pyrazolic, the linear bi‐pyrazolic units and the bipyrazolic tripods. We recall here that the tetrapyrazolic tripods present higher complexation ability towards the transition metal cations compared with the mono‐ and bi‐pyrazolic ligands 4–6. We can thus say that the phenomenon of transport is governed by the complexation ability of ligands.…”
Section: Resultsmentioning
confidence: 87%
“…In our recent works, a series of acyclic pyrazole compounds containing one, two, three or four pyrazole rings were prepared and demonstrated to extract only the heavy metal cations,1–6 when the macrocyclic pyrazolic compounds expected to form stable complexes both with heavy and alkali metals 7–9…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18] However, the present ligands 5-7 towards others metals. We can thus suggest an important selectivity for these ligands towards copper and lead.…”
Section: Liquid-liquid Extraction Of Individual Cationsmentioning
confidence: 93%